Efficient Access to 3D Mesoscopic Prisms in Polymeric Soft Materials. Issue 11 (15th March 2021) - Lyu, Xiaolin; Huang, Hanlin; Tang, Zhehao; Luo, Longfei; Luo, Wenjun; Yu, Yan; Shen, Zhihao; Fan, Xing‐He; Zou, Zhigang
Abstract: The preparation of 3D functional isolated mesoscopic assemblies remains a challenge in the self‐assembly of polymers. Here, well‐defined 3D hexagonal and hexagram prisms with uniform dimensions are acquired by the crystallization of the inclusion complex composed of a crystalline molecule tris‐ o ‐phenylenedioxycyclotriphosphazene (TPP) and a block copolymer. The crystalline TPP plays an important role in the self‐assembling process. The faceted morphologies of the hexagonal and hexagram prisms are infrequent in the self‐assembly field of soft materials. The formation of the prisms experiences a 3D growth mechanism. The epitaxial growth, accompanied by the heterogeneous nucleation in the edges, yields the growth of inclusion crystals. This study provides a path to construct well‐defined polymeric soft materials with broad utility based on numerous supramolecular complexes. Abstract : Well‐defined and faceted hexagonal and hexagram prisms are prepared by the crystallization of a coil‐crystalline supramolecular block copolymer, which are infrequent in the self‐assembly field of soft materials. The epitaxial growth, accompanied by the heterogeneous nucleation on the edges, yields the growth of inclusion crystals. Based on numerous supramolecular complexes, polymeric soft materials with various applications can be constructed.